The analysis of distance learning effectiveness both synchronous and asynchronous in learning business English - Efendi, Erfan; Aly, Abdul Hamid; Purnawan, I Kadek (Journal of English Language and Pedagogy, 2024)
This study examines the effectiveness of Synchronous Distance Learning (SDL) and Asynchronous Distance Learning (ADL) in the teaching and learning process of Business English. The research aims to evaluate the individual and combined effects of SDL and ADL on students' learning achievement, providing insights for educators to design and implement appropriate teaching strategies. The study involved 30 university students enrolled in a Business English course, utilizing a questionnaire-based data collection method with a Likert scale. Data were analyzed using multiple regression analysis to test three hypotheses regarding the impact of SDL, ADL, and their combined implementation on learning outcomes. The findings revealed that neither SDL nor ADL significantly influenced students' Business English learning achievement, and their combined application also showed no measurable effect. These results highlight potential limitations in applying SDL and ADL as standalone approaches for teaching skill-intensive subjects like Business English, which require interactive and practice-based learning. The study underscores the importance of addressing challenges such as technological barriers, digital literacy gaps, and the need for innovative instructional designs to enhance the effectiveness of distance learning. It suggests adopting a hybrid learning model that leverages the strengths of both SDL and ADL while incorporating interactive and collaborative elements tailored to the unique demands of Business English education.